The United States Copper Industry and the Tariff - Pettengill, Robert B. (Quarterly Journal of Economics, 1931)
United States copper consumption increasing at a faster rate than production but not yet in excess of the latter, 142. — Apparent excess of consumption in 1930 due to decline in exports, 143. — Copper Exporters, Inc., organized in 1926, to regulate the foreign marketing of our copper, 145. — The Copper Institute, a trade association, formed in 1927, 146. — Prices rose to peak in April, 1929, were pegged at eighteen cents for a year, and fell below ten cents in October, 1930, 148. — Output restriction announced in November, 148. — Large potential new mine supply in next five years, 149. — Short-run outlook not bright, 151. — Long-run position sound, indicated by calculation of probable world demand in 1940 for primary copper, 152. — Conclusions as to future price, 154. — A tariff today would not help the industry, might in ten years, 155. — Real need is lower tariffs for United States and world, 156.